Volatile Fatty Acid Production from Baker’s Yeast Industry Effluent - Altinbas, Mahmut; Kara, Ceren; Hasanoglu, Aysel (Springer Science and Business Media LLC, 2018)
Baker’s Yeast Industry (BYI) effluent was one of the strongest wastewaster type that contains high amount of organic matter, salinity, nitrogen and sulphate. These characteristics were unfavorable for the application of wastewater treatment. For this reason, a recovery-oriented approach was applied for the appropriate conditions to increase the Volatile Fatty Acid (VFA) production potential of BYI. In this concept, hydrolysis anaerobic Membrane Bioreactor was used to produce VFAs. The hydrolysis reactor was operated between 2.5 and 13.4 days in Hydraulic Retention Time, at a thermophilic temperature (55 °C) and at pH of 4.5–8 for 858 days. The highest biomass concentration was 26 g L−1 in the reactor, and mainly acetate, propionate and butrate production was observed. The highest acetate production was seen at pH 7 with an average concentration of 25,930 mg L−1. The highest total VFA production yield was 0.98 g VFA–COD g−1 COD. It was concluded that carrying out hydrolysis and acidification reactions at neutral pH was better as long as methane production could be avoided. In addition, a VFA-rich stream with free suspended solids could be obtained with the 0.05 µ pore diameter submerged membrane. Population dynamics remained quite stable and rich in biomass consortia throughout the study. It was suggested that a high commercial value could be obtained, especially by recovering acetate from the hydrolysis reactor’s outlet stream.